Being on Target: Visual Information during Writing Affects Effective Connectivity in Parkinson's Disease. (10th February 2018) - Nackaerts, Evelien; Michely, Jochen; Heremans, Elke; Swinnen, Stephan; Smits-Engelsman, Bouwien; Vandenberghe, Wim; Grefkes, Christian; Nieuwboer, Alice
Highlights: Patients with PD had impaired right hemispheric visuomotor integration. Patients with PD and controls switch similarly between internal and external modes of motor control. Visual cueing for handwriting enhances online visuomotor connectivity in the brain without improving motor output. Abstract: A common motor symptom of Parkinson's disease (PD) is micrographia, characterized by a decrease in writing amplitude. Despite the relevance of this impairment for activities of daily living, the underlying neural network abnormalities and the impact of cueing strategies on brain connectivity are unknown. Therefore, we investigated the effects of visual cues on visuomotor network interactions during handwriting in PD and healthy controls (HCs). Twenty-eight patients with early disease, ON dopaminergic medication, and 14 age-matched controls performed a pre-writing task with and without visual cues in the scanner. Patients displayed weaker right visuo-parietal coupling than controls, suggesting impaired visuomotor integration during writing. Surprisingly, cueing did not have the expected positive effects on writing performance. Patients and controls, however, did activate similar networks during cued and uncued writing. During cued writing, the stronger influence of both visual and motor areas on the left superior parietal lobe suggested that visual cueing induced greater visual steering. In the absence of cues, there was enhanced coupling between parietal and supplementary motor areas (SMA) in line with previous findings in HCs during uncued motor tasks. In conclusion, the present study showed that patients with PD, despite their compromised brain function, were able to shift neural networks similar to controls. However, it seemed that visual cues provided a greater accuracy constraint on handwriting rather than offering unequivocal beneficial effects. Altogether, the results suggest that the effectiveness of using compensatory neural networks through applying external stimuli is task dependent and may compromise motor control during writing.